Computational thinking levels of non-computing students through peer learning strategies in online collaborative learning environment / Ahmad Syihan Fadzli Khairi ... [et al.] - Khairi, Ahmad Syihan Fadzli; Mohd Zaid, Norasykin; Abdullah, Zaleha; Abd Halim, Noor Dayana; Md Noor, Harrinni; Syamsul Nor Azlan Mohamad, Syamsul Nor Azlan; Cheong, Tau Han (Universiti Teknologi MARA, 2024)
This study aimed to evaluate the computational thinking skills of students majoring in Chemistry who participated in computational thinking activities before and after the intervention. Employing a quantitative research paradigm with a survey research design, the study involved 29 students from the Bachelor of Science in Education program who took Programming Language as an elective. A purposive sampling technique was used to select the participants. The Computational Thinking Scale was utilized to measure the students' computational thinking skills. Results indicated that while students demonstrated high computational thinking skills comparable to those with computing backgrounds, the implementation of peer learning strategies did not yield significant effects on skill development. Additionally, the study explored peer learning patterns during computational thinking activities, revealing that students exhibited cognitive knowledge, planning, assessment, and monitoring characteristics. A positive and robust relationship was found between the stages of computational thinking skills and the four observed peer learning patterns. Students' perceptions of their computational thinking skills showed high problem-solving abilities but lower scores in critical and cooperative thinking. This study provides valuable insights for researchers and educators in designing computational thinking activities and offers an overview of the computational thinking tendencies among prospective teachers in Malaysia.